Public Perception of Social Entrepreneurship and Its Impact on Social Participation in Indonesia - Destikarini, Fartina; Efniar, Efniar; Wibowati, Januar Ida (Eastasouth Institute, 2025)
Social entrepreneurship has emerged as a critical approach to addressing social and environmental challenges while promoting community participation. This study explores public perceptions of social entrepreneurship and its impact on social participation in Indonesia through a qualitative analysis of interviews with five informants. The findings reveal that social entrepreneurship is widely viewed as a mechanism for solving social problems and fostering active engagement within communities. Key themes identified include the understanding and definition of social entrepreneurship, its positive influence on social participation, barriers to involvement, perceived benefits, and the critical role of education and awareness campaigns. The study concludes that while public perception is generally positive, significant efforts are needed to address barriers and enhance participation through increased education, awareness, and support. These insights contribute to the discourse on social entrepreneurship in developing countries and highlight pathways for enhancing its impact in Indonesia.